Notes on Some Interesting Sporocarp-Inhabiting Fungi Isolated from Xylarialean Fungi in Japan - Wasiatus Sa’diyah; Akira Hashimoto; Gen Okada; Moriya Ohkuma (Diversity, 2021)
The diversity of sporocarp-inhabiting fungi (SCIF) was examined using six samples of xylarialean fungi from two different forests in Ibaraki Prefecture, Japan: a moist forest in the Sakuragawa area and an urban dry forest in the Tsukuba area. These fungi were enumerated using direct observation and dilution plate methods. We obtained 44 isolates, and careful morphological and molecular phylogenetic studies of these isolates revealed that approximately 30% of the operating taxonomic units were undescribed or cryptic species related to known fungi. Although typical mycoparasitic fungi, such as helotialean fungi and Trichoderma spp., were not isolated, the genera Acremonium, Acrodontium, and Simplicillium were detected. Comparisons of SCIF communities between the two forests suggested that the number of isolated species in the Sakuragawa area was lower than that in the Tsukuba area. Soil-borne fungi, such as Aspergillus, Beauveria, Penicillium, and Talaromyces, or polypores/corticioid mushrooms, are frequently detected in the Tsukuba area. Factors affecting SCIF communities in the two forests are discussed. Some noteworthy fungi are briefly described with notes on taxonomy, ecology, and molecular phylogeny.